2021
DOI: 10.1021/acssuschemeng.1c00574
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Fibers Derived from Oleic Acid-Functionalized Lignin via Thermostabilization Accelerated by UV Irradiation

Abstract: Lignin is a biorenewable precursor source suitable for the production of low-cost carbon fibers. In this work, softwood lignin was chemically modified with fatty acids to employ UVtriggered oxidative reactions occurring at long alk(en)yl chains as a pretreatment prior to thermostabilization. The chemical transformation of oleic acid-functionalized lignin (OAFL) under the UV irradiation was the free radical-based cross-linking reaction assisted by atmospheric oxygen, which successfully formed oxidatively cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…100 Similarly, the addition of nanocrystalline cellulose (NCC) into lignin can also yield LCFs with good fiber geometry through direct carbonization without the stabilization step. 99 Apart from lignin blending with polymers, some interesting methods have also been developed to accelerate the stabilization of LCFs, such as stabilization under HCl/air atmosphere, 124 stabilization assisted by UV radiation, 131 and phosphorus functionalization of lignin. 132 Liu et al prepared a novel precursor of lignosulfonate-acrylonitrile-itaconic acid terpolymer and studied its thermal stabilization.…”
Section: Stabilizationmentioning
confidence: 99%
“…100 Similarly, the addition of nanocrystalline cellulose (NCC) into lignin can also yield LCFs with good fiber geometry through direct carbonization without the stabilization step. 99 Apart from lignin blending with polymers, some interesting methods have also been developed to accelerate the stabilization of LCFs, such as stabilization under HCl/air atmosphere, 124 stabilization assisted by UV radiation, 131 and phosphorus functionalization of lignin. 132 Liu et al prepared a novel precursor of lignosulfonate-acrylonitrile-itaconic acid terpolymer and studied its thermal stabilization.…”
Section: Stabilizationmentioning
confidence: 99%
“…Our previous work successfully demonstrated that GPL can be utilized as a versatile starting material to obtain lignin derivatives due to the presence of epoxide rings highly subject to nucleophilic addition reactions. 45 In this study, NaN 3 and carboxylic acids containing carbon−carbon triple bonds (alkynoic acids) reacted with epoxide rings of GPL to introduce azide and alkynoate groups to lignin, respectively (Scheme 1a). As shown in Figure 1a, no absorption bands corresponding to epoxide rings (913 cm −1 ; peak a) were observed from the FTIR spectra of APL, PPL, HPL, and UPL after the ring-opening addition reaction, demonstrating that all ring structures of GPL were opened by nucleophilic addition reactions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The synthesis of glycidylated phenolated lignin (GPL) is described elsewhere. 45 Softwood lignin (150 g) and phenol (150 g) were reacted in a closed stainless-steel high-pressure reactor (Parr 4523 benchtop reactor with the model 4848 reactor controller, USA) at 275 °C for 1 h. The mixture was then cooled down to 200 °C, followed by distillation for 1 h under reduced pressure. The resulting solidified phenolated lignin (PL) was ground into a fine powder, which was subsequently rinsed with deionized water on a filter paper until the aqueous filtrate was neutral and dried at 80 °C for 15 h in a vacuum oven.…”
Section: ■ Introductionmentioning
confidence: 99%
“…현재 상업적으로 생산되는 탄소 소재들의 원료 대부분은 화석연료에서 유래한 콜타르, 피치, polyacrylonitrile (PAN) 등이다. 특히 PAN은 가격이 비싸서 이를 재생 가능한 바이오매스로 대체하기 위한 많은 연구가 진행되고 있다 (Sudo and Shimizu, 1992;Kubo et al, 1998;Kadla et al, 2002;Kubo and Kadla, 2005;Ibrahim et al, 2010;Qin and Kadla, 2011;Baker et al, 2012;Chen et al, 2021;Kang et al, 2021).…”
Section: Acknowledgmentunclassified
“…Most of the current commercially produced carbon materials nowadays are coal tar, pitch, and polyacrylonitrile (PAN) that are derived from fossil fuels. PANs in particular are expensive, and therefore many studies are being conducted to replace them with renewable biomass (Sudo and Shimizu, 1992;Kubo et al, 1998;Kadla et al, 2002;Kubo and Kadla, 2005;Ibrahim et al, 2010;Qin and Kadla, 2011;Baker et al, 2012;Chen et al, 2021;Kang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%